IMPLEMENTATION OF ENVIRONMENTAL CARE CHARACTER EDUCATION AT SDN ABCD BANDUNG - Vitriasari, Leny; Sapriya; Wahyu Wandani, Roni (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
This research aims to describe the program and obstacles in implementing environmental care character education at SDN ABCD Bandung. This research uses a qualitative descriptive research method. The subjects of this research are the principal, teachers and students. The research object is the implementation of character education that cares about the environment. Data collection instruments use observation, interviews and documentation. The data was analyzed using data reduction, data display and verification techniques. Test the validity of the data using triangulation of techniques and sources. The research results show that (1) the implementation of environmentally caring character education is carried out through school policies, curriculum implementation, participatory environmental activities and management of environmentally friendly supporting facilities. Implementation has reached the moral action stage, but has not yet reached the habitual stage. (2) the obstacles are students' awareness of caring for the environment, sorting waste, and lack of understanding of the vision and mission, lack of consistency in teacher preparation in student learning and understanding, work teams are less solid, creativity is not consistent, students are less active in extracurricular activities, there are damaged facilities and students have not consistently brought healthy food supplies.